2011
DOI: 10.12962/j20882033.v22i2.63
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Stakeholder Psychological Empowerment on Project Success

Abstract: The relationship between psychological empowerment of stakeholders and project success is an important thing that must be known by project manager. This research developed and tested the model to predict how well the impact of stakeholder psychological empowerment on project success. Stakeholder psychological empowerment was defined to have five indicator variables covering intrinsic motivation, opportunity to perform, ability to perform, task behaviors, and contextual behaviors. Meanwhile, project success can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…Empowered employees have the competence to execute the tasks in a timely manner. Chandra et al (2011) found a significant positive effect of stakeholders' psychological empowerment on project success. Thus, we hypothesize:…”
Section: Theory and Hypothesesmentioning
confidence: 90%
“…Empowered employees have the competence to execute the tasks in a timely manner. Chandra et al (2011) found a significant positive effect of stakeholders' psychological empowerment on project success. Thus, we hypothesize:…”
Section: Theory and Hypothesesmentioning
confidence: 90%
“…Stakeholders can be identified in terms of the way they carry out their roles with the attributes described by [4,5], where the classification of stakeholder mapping is determined by influence, legitimacy, and urgency of interests. This means that stakeholders are classified based on their roles because every individual has a different role and interest.…”
Section: Introductionmentioning
confidence: 99%
“…Bryson (2004) defines stakeholders are any individual, group, or organization that has an interest in organizational resources or results or is also influenced by these results. Another definition of stakeholders is as a community, both individuals and groups, which have legitimacy, power, and importance to the success of the company (Chandra, Indarto, Wiguna, & Kaming, 2011). The role of stakeholders can be influenced by knowledge.…”
Section: Introductionmentioning
confidence: 99%